Differential water uptake response in Indian mustard genotypes with varying seed coat colour - SUNIL SWAMI; SANGITA YADAV; SHIV K. YADAV; A. DAHUJA; D.K. YADAVA (Seed Research, 2026)
The present investigation was undertaken with the objectives to study the water uptake in conventional and quality Indian mustard [Brassica juncea Czern & Coss] genotypes of different seed coat colour under freely and restricted water conditions. The material consisted of eight genotypes of Indian mustard in which four genotypes each were of conventional and quality types. The seed of these genotypes varied for seed coat color i.e. four black seeded and four yellow seeded. All these genotypes were initially assessed for the seed quality parameters viz.; percent moisture content, test weight and germination per cent and subsequently, for their imbibition behavior under free and limited available water conditions. The studies were carried out in both fresh and controlled deteriorated seeds. It was found that imbibitional rate were significantly associated with the seed colour as well as quality of the genotypes. The fresh and controlled deteriorated seeds with yellow seed coat had the highest water uptake, while black seed had the lowest water uptake ratio under both conditions of water availability. In addition, decrease in imbibition of deteriorated yellow seeded genotypes could be attributed to lowered ability of its testa to withhold moisture. Imbibitional damage during aging could be one of the factors which contribute to seed quality differences among Indian mustard genotypes with varying seed coat colour.